2009
DOI: 10.1542/peds.2008-0931
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Prescription ADHD Medication Abuse Is Rising Along With Prescriptions for These Medications

Abstract: The sharp increase, out of proportion to other poison center calls, suggests a rising problem with teen ADHD stimulant medication abuse. Case severity increased over time. Sales data of ADHD medications suggest that the use and call-volume increase reflects availability, but the increase disproportionately involves amphetamines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 27 publications
1
72
0
3
Order By: Relevance
“…Stimulant medications are both more effective at treating ADHD symptoms 53 and much more commonly misused than nonstimulant medications. Pediatricians are thus in a position to prescribe a medication that can reduce both ADHD symptoms and the risk of developing an SUD and simultaneously pose a risk for abuse and diversion.…”
Section: Stimulant Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulant medications are both more effective at treating ADHD symptoms 53 and much more commonly misused than nonstimulant medications. Pediatricians are thus in a position to prescribe a medication that can reduce both ADHD symptoms and the risk of developing an SUD and simultaneously pose a risk for abuse and diversion.…”
Section: Stimulant Medicationsmentioning
confidence: 99%
“…59,69 Indeed, short-acting medications are more likely to be misused or abused, and amphetamine preparations are misused and abused more frequently than methylphenidate preparations. 53,70,71 3 ADHD symptoms must be present during childhood; thus, particular caution is warranted before making a new diagnosis of ADHD, especially in an adolescent. Although it is possible that symptoms in childhood were unnoticed, adolescents sometimes attempt to get a stimulant prescription by feigning symptoms of ADHD.…”
Section: Diversion Of Stimulant Medicationsmentioning
confidence: 99%
“…28 We found that stimulant medications were prescribed to adolescents at an increasing rate over the study period, similar to previously observed trends. 29 35 Potential associations between regional prescribing patterns and rates of misuse are complex and difficult to observe when using broad geographic regions.…”
Section: Figurementioning
confidence: 99%
“…Between 1998 and 2005, there was a 133% increase in amphetamine product prescriptions and a 52% increase in methylphenidate products, for teenagers and preteenagers in the US (Setlik et al, 2009). According to US government data, from 1998 to 2007, total amphetamine prescriptions increased by about 11.7 million, or 463% (Stix, 2009).…”
mentioning
confidence: 99%